Review of avian species richness in coastal Andhra Pradesh (Zoological Records and Reviews, 2026)
The coastal zone of Andhra Pradesh, extending approximately 974 km along the Bay of Bengal, encompasses a mosaicof mangrove forests, estuarine mudflats, sandy beaches, backwater lagoons, saltpans, and deltaic wetlands thatcollectively constitute one of the most significant avian habitats on the eastern coast of India. This review synthesisespublished and grey literature on avian species richness in coastal Andhra Pradesh from 1980 to 2020, integrating datafrom systematic ornithological surveys, waterbird censuses, eBird citizen science records, and museum specimendatabases. A total of 412 bird species belonging to 72 families are documented from the coastal zone, including 187resident breeding species, 148 migratory species (Palearctic and intra-Asian migrants), and 77 species with uncertain orirregular status. The Godavari and Krishna river deltas emerge as the highest-richness zones, supporting 68.4% and62.1% of all documented coastal species respectively. Critically threatened species include the Spoon-billed Sandpiper(Calidris pygmaea, CR), Sociable Lapwing (Vanellus gregarius, CR), and Indian Skimmer (Rynchops albicollis, EN).Habitat loss driven by aquaculture expansion, industrial development, and sea-level rise is identified as the primary threat to coastal avian diversity. Priority conservation recommendations include the designation of three additional Important Bird and Biodiversity Areas (IBAs) along the northern Andhra Pradesh coast and enhanced legal protection for inter-tidal mudflat habitats outside existing sanctuary boundaries.
Keywords: conservation; estuarine wetlands; Bay of Bengal; Important Bird Areas; mangroves; migratory; waterbirds; avian diversity; coastal Andhra Pradesh; birds